2014
DOI: 10.5664/jcsm.3444
|View full text |Cite
|
Sign up to set email alerts
|

Depression May Reduce Adherence during CPAP Titration Trial

Abstract: Study Objectives: Depression is a risk factor for medication non-compliance. We aimed to identify if depression is associated with poorer adherence during home-based autotitrating continuous positive airway pressure (autoPAP) titration. Design: Mixed retrospective-observational study. Setting: Academic center. Participants: Two-hundred forty continuous positive airway pressure-naïve obstructive sleep apnea (OSA) patients. Measurements:Patients underwent approximately 1 week of home-based autoPAP titration with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 50 publications
2
37
0
2
Order By: Relevance
“…Two other small studies found no association between CPAP use and depression [60,61]. In a recent study, the investigators conducted 1 week of home-based auto-PAP titration and monitored adherence objectively on 240 CPAP-naïve OSA patients [62]. Multiple linear regression analysis revealed that depression significantly predicted fewer hours of auto-PAP use [62].…”
Section: Relationship Between Depression and Cpap Adherencementioning
confidence: 97%
See 1 more Smart Citation
“…Two other small studies found no association between CPAP use and depression [60,61]. In a recent study, the investigators conducted 1 week of home-based auto-PAP titration and monitored adherence objectively on 240 CPAP-naïve OSA patients [62]. Multiple linear regression analysis revealed that depression significantly predicted fewer hours of auto-PAP use [62].…”
Section: Relationship Between Depression and Cpap Adherencementioning
confidence: 97%
“…In a recent study, the investigators conducted 1 week of home-based auto-PAP titration and monitored adherence objectively on 240 CPAP-naïve OSA patients [62]. Multiple linear regression analysis revealed that depression significantly predicted fewer hours of auto-PAP use [62]. However, most of the previous studies did not control for confounders, such as OSA symptoms (e.g., daytime sleepiness), comorbid conditions of OSA and depression (e.g., insomnia and anxiety), or use and compliance with antidepressant medications which may influence CPAP adherence.…”
Section: Relationship Between Depression and Cpap Adherencementioning
confidence: 99%
“…This decision was based on research indicating a steadily increasing incidence of OSA in US veterans; most recent estimates show that the prevalence of OSA among veterans treated in the VA system ranges from 3% to 8% . Although there are no population‐based studies of PAP compliance in veterans, these patients reportedly have a high prevalence of comorbid depression, anxiety, poverty, and post‐traumatic stress disorder, all of which are associated with reduced PAP adherence, suggesting that many veterans might be potential candidates for HGNS therapy . Once the Inspire HGNS was placed on the Federal Supply Schedule, indications for its use are determined by VA treating physicians (both otolaryngology and sleep medicine) in collaboration with the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Results regarding the effect of depression on PAP adherence are inconsistent, 6 but a recent study indicated that depressed patients with OSA might have poorer compliance with PAP treatment. 36 Furthermore, a number of studies have indicated a bidirectional relationship between poor sleep and depression; some have suggested that sleep difficulties may lead to or exacerbate depression and that by improving sleep quality it is possible to improve symptoms of depression as well. 37,38 OSA severity was not related to depression in our study and others have reported similar results, suggesting that depression is more related to disrupted sleep and sleepiness than OSA severity per se.…”
Section: Table 4-predictivementioning
confidence: 99%